Iniquities in the access to renal transplant for patients with end-stage chronic renal disease in Brazil Iniquidades no acesso ao transplante renal para pacientes com doença renal crônica terminal no Brasil - Elaine Leandro Machado; Waleska Teixeira Caiaffa; Cibele Comini César; Isabel Cristina Gomes; Eli Iola Gurgel Andrade; Francisco de Assis Acúrcio; Mariangela Leal Cherchiglia (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The objective of this present study is to analyze individual and contextual factors associated with access to renal transplant in Brazil. An observational, prospective and non-concurrent study was carried out, based on data from the National Database on renal replacement therapies in Brazil. Patients undergoing dialysis between 01/Jan/2000 and 31/Dec/2000 were included and monitored up to the point of transplant, death or until the end of the study period. Variables that were analyzed included: individual variables (age, sex, region of residence, primary renal disease, hospitalizations); and context variables concerning both the dialysis unit (level of complexity, juridical nature, hemodialysis machines and location) and the city (geographic region, location and HDI). Proportional hazard models were adjusted with hierarchical entry to identify factors associated with the risk of transplant. The results point to differentials in access according to socio-demographic, clinical, geographic and social factors, indicating that the organ allocation system has not eliminated avoidable disparities for those who compete for an organ in the nationwide waiting list. O objetivo deste estudo é analisar os fatores individuais e contextuais associados ao acesso ao transplante renal no Brasil. Realizou-se um estudo observacional, prospectivo, não concorrente, a partir de dados da Base Nacional em terapias renais substitutivas, no Brasil. Foram incluídos pacientes incidentes em diálises entre 01/jan/2000 e 31/dez/2000, acompanhados até o transplante, óbito ou final de 2003. Variáveis individuais (idade, sexo, região de residência, doença renal primária, internações) de contexto da unidade de diálise (nível de complexidade, natureza jurídica, máquinas de hemodiálise e localização) e do município (região geográfica, localização e Índice de Desenvolvimento Humano) foram analisadas. Ajustaram-se modelos de riscos proporcionais com entrada hierárquica para identificar fatores associados ao risco de transplante. Os resultados apontam diferenciais no acesso segundo fatores sociodemográficos, clínicos, geográficos e sociais ao transplante, indicando que o sistema de alocação de órgão não tem eliminado disparidades evitáveis para aqueles que concorrem a um órgão na lista de espera única.